Oral Carriage Rate of Candida Species in Diabetic Patients - Khazal, *Faris Abdul Kareem; Mahran, Adnan; Al-Hasnawi, Huda Hadi (AL-Kindy College Medical Journal, 2006)
Background: It is well known that oral carriageof Candida species increase in many situations, likeobesity, debility, leukemia, viral infection, use ofcertain drugs in addition to diabetes mellitus.Objective: find the relation between diabetes andits control on oral carriage of Candida.Methods: Thirty four hundred oral swabs fromdiabetic patients 67% are females and 33% aremales, 41.7% are type 1 diabetes and 58.3% are type2.different culture media are used.Results: we found that 37.9% of diabetics had oralcarriage, older age group had more but thedifference is not significant statistically P>0.05, inaddition females carry more Candida than malesP